CORRECTING THE STUDENTS’ ERROR IN WRITING ESSAY - Rahayu, Nanik Sri (Pusat Pengembangan Bahasa IAIN Tulungagung, 2010)
Writing an essay is not always a simple job for the foreign language learners since writing is considered to be the advanced language skill that can be successfully achieved if they have mastered the target language rule. Besides, they don?t have enough background knowledge and seldom practice it outside the class. Thus, comitting error in the students?writing essay is a comon phenomena. The way the teacher corrects to those errors reflects his concern for the students that can motivate them in the teaching learning process. Furthermore, the students? error is not always a bad thing in the teaching learning process. If the teacher could respond it wisely, those errors can tell the teacher about the students? development in acquiring the writing skill.